Chemical Composition and Antibacterial Activity of Plumeria alba L., Polianthes tuberosa L., and Cananga ordorata L. Flowers Essential Oils as Bioadditives in Transparent Solid Bath Soap - Ariani, Sri Retno Dwi; Mitsalina, Aufa Vib; Wathon, Muhammad Hizbul (Universitas Jenderal Soedirman, 2024)
This study aimed to analyze the chemical components and antibacterial activity of essential oils from kamboja (Plumeria alba L.), sedap malam (Polianthes tuberosa L.), and kenanga (Cananga ordorata L.) flowers against Staphylococcus aureus ATTC 25923. Additionally, the study explored the application of these essential oils as bio additives in transparent solid bath soap. The research consisted of several stages: isolation and identification of chemical components of essential oils using the GC-MS Method, transparent solid bath soap formulation, antibacterial activity test of essential oils and transparent solid bath soaps against Staphylococcus aureus ATTC 25923, organoleptic test (color, aroma, transparency, solidity, and foam) and quality test of transparent solid bath soaps (pH, water content, foam stability, saponification number, and transparency). The essential oils extracted from kamboja, sedap malam, and kenanga flowers were found to contain 17, 20, and 20 compounds, respectively. Based on the result of GC-MS analysis showed that the predominant chemical components in each essential oil were 1,1’-oxydi-2-propanol (21.01%) for kamboja, benzyl ethanoate (24.52%) for sedap malam, and caryophyllene (43.77%) for kenanga. Transparent solid bath soaps with the highest antibacterial activity against S. aureus ATTC 25923 were obtained in the formula added with kamboja, sedap malam and kenanga flowers essential oils at 3.0%, 3.0%, and 3.0%, respectively, with respective inhibitory power of 14.48 mm (strong), 13.73 mm (strong) and 13.56 mm (strong) in diameter. Organoleptic tests revealed that each soap type exhibited characteristic of the respective flower. All soap types demonstrated good quality based on parameters such as pH, water content, foam stability, saponification number and transparency. Keywords: Cananga ordorata L., essential oil, Plumeria alba L., Polianthes tuberosa L., transparent solid bath soap